Factors Hindering Quality of Antenatal Care Among Pregnant Women Attending Primary Healthcare in Ede, Osun State, Nigeria - Aderinto Adebimpe; Oshineye Adeola; Olarinmoye Abayomi; Akin Oyebade; Akin Ajayi; James Atolagbe (Pan-African Journal of Health and Environmental Science, 2025)
Background: Quality antenatal care is crucial for achieving Sustainable Development Goals in both developing and developed countries. This study aimed to identify factors hindering the quality of antenatal care among pregnant women attending primary healthcare facilities in Ede South, Osun State, Nigeria.